Development of Worship Product Design in Meeting Muslim Needs in Southeast Asia - Marzuki Ibrahim; Ribangun Bamban Jakaria (Madrosatuna: Journal of Islamic Elementary School, 2020)
The heyday of Islam began in the middle of the 7th century, but today we find that Muslims are struggling to make a name for themselves in pioneering science and technology. That should not be the case, because many of the creations enjoyed today are actually based on creations from Islamic civilization and not from the West. Therefore, to restore this glory, a new plan must start from now. Among other things, through the development of worship products for the use of Muslims, especially in Southeast Asia. To make the idea of ​​developing this worship product clear, several examples of existing worship products are presented and discussed their weaknesses from a design perspective. Five examples of innovative products specifically designed for the needs of Muslims are clarified. The reason for the need for innovation in worship products is also statistically discussed in depth based on the growth of Muslims, with more than 1.6 billion Muslims. Furthermore, as many as nine groups of worship products that have the potential to be developed are products for prayer, recitation, pilgrimage, and umrah. Finally, design features need to be considered for developing worship products. It is hoped that the innovative products of worship services will generate wealth to improve the quality of life of Muslims throughout the world.